2010
DOI: 10.1007/s00280-010-1349-2
|View full text |Cite
|
Sign up to set email alerts
|

Renal safety and efficacy of cisplatin-based chemotherapy in patients with a solitary kidney after nephroureterectomy for urothelial carcinoma of the upper urinary tract

Abstract: Cisplatin-based chemotherapy can be administered in the majority of patients with UUT-UC with a solitary kidney after nephroureterectomy without inducing a serious AE, and provides acceptable efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, the majority of patients with a solitary kidney underwent cisplatin-based chemotherapy without serious adverse events20. We also believe that nephrotoxicity to the single renal unit is not a major concern in adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…However, the majority of patients with a solitary kidney underwent cisplatin-based chemotherapy without serious adverse events20. We also believe that nephrotoxicity to the single renal unit is not a major concern in adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Although very few studies have examined the effect of cisplatin‐based adjuvant chemotherapy after RNU on renal function, rare cases of hemodialysis have been reported …”
Section: Systemic Chemotherapy and Othersmentioning
confidence: 99%
“…However, Lene et al recently showed that renal cell carcinoma patients with surgically-induced CKD (CKD-S) have a relatively low risk of progressive renal function decline, whereas those with medically-induced CKD (CKD-M) have an increased risk [ 20 ]. In addition, a previous report from Korea showed that cisplatin-based chemotherapy was safe in the majority of patients who underwent nephroureterectomy [ 21 ]. It is plausible that the CKD-S patients, who underwent nephroureterectomy or who have ipsilateral hydronephrosis and an intact solitary-functioning kidney without medical comorbidities, have some potential endurance for nephrotoxicity in cisplatin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%